Assessment of geogrids in gravel roads under cyclic loading - Azza Mohamed Elleboudy; Nasser Mosleh Saleh; Amany Gouda Salama (Alexandria Engineering Journal, 2017)
Performance of geogrid in gravel roads subjected to repeated loads was investigated through laboratory testing in the laboratory of faculty of engineering at Shoubra and finite element analysis. Twenty two laboratory model tests under cyclic loading were conducted on road sections consisting of base course layer with and without geogrid reinforcement overlaying weak subgrade. Parameters investigated included base layer thickness, grid aperture size, geogrid tensile strength, number of geogrid layers, and geogrid location. The experimental results indicated that the inclusion of one geogrid sheet placed at the base of course layer reduced the vertical deformation by about 18 to 64% depending on the base course layer thickness. The vertical deformation depth increased rapidly during the initial load cycles; thereafter the rate of settlement is reduced as the number of loading cycles increased. The most effective location of geogrid was found to be in the top quarter of the base course layer. When the results of the laboratory tests were compared with the analytical solution using finite element program ABAQUS, the FE results were in good agreement with the experimental test results.